2020
DOI: 10.1097/xce.0000000000000198
|View full text |Cite
|
Sign up to set email alerts
|

Associations of adiponectin and leptin with brain natriuretic peptide in African Americans: the Jackson Heart Study

Abstract: Background Brain natriuretic peptide (BNP) is elevated in decompensated systolic and diastolic heart failure. The plasma levels of adipokines, such as adiponectin and leptin, may provide evidence for mechanistic differences in BNP concentrations. African-American-specific associations are limited in the literature. The objective of this study was to evaluate the associations of adiponectin and leptin with BNP among African Americans. Methods Linear and logistic regressions were used to test the associations be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…The obtained results corroborate data presented in recent publications showing that increased blood ADP concentration is a factor in the poor prognosis in CHF patients [12][13][14][15][16][17]. The association of poor prognosis in CHF patients with higher blood ADP concentration, which should, theoretically, exert cardioprotective action, is known as the "ADP paradox", and is recognized as the result of ADP resistance [16]. On the other hand, our results are inconsistent with those of a study by Mayer et al [19], who showed that the associations between higher blood ADP concentration and patient mortality and risk of CHF disappeared after data adjustment for blood NT-proBNP concentration.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The obtained results corroborate data presented in recent publications showing that increased blood ADP concentration is a factor in the poor prognosis in CHF patients [12][13][14][15][16][17]. The association of poor prognosis in CHF patients with higher blood ADP concentration, which should, theoretically, exert cardioprotective action, is known as the "ADP paradox", and is recognized as the result of ADP resistance [16]. On the other hand, our results are inconsistent with those of a study by Mayer et al [19], who showed that the associations between higher blood ADP concentration and patient mortality and risk of CHF disappeared after data adjustment for blood NT-proBNP concentration.…”
Section: Discussionsupporting
confidence: 91%
“…6). The obtained results corroborate data presented in recent publications showing that increased blood ADP concentration is a factor in the poor prognosis in CHF patients [12][13][14][15][16][17]. The association of poor prognosis in CHF patients with higher blood ADP concentration, which should, theoretically, exert cardioprotective action, is known as the "ADP paradox", and is recognized as the result of ADP resistance [16].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations